2013
DOI: 10.3329/fmcj.v8i1.16890
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Laboratory Tests to Diagnose Helicobacter pylori Infection

Abstract: Helicobacter pylori is a Gram negative bacteria which causes chronic gastritis, peptic ulcer disease, primary B-cell gastric lymphoma, and adenocarcinoma of the stomach. There are a set of laboratory tests to diagnose H. pylori infection with a variable accuracy, they are divided into non-invasive tests and invasive tests. Non-invasive tests include serology, urea breath test (UBT) and stool antigen test (SAT). Invasive tests include rapid urease test (RUT), histology and culture. This cross sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This result is very similar to that of another study performed in Bangladesh, which showed a sensitivity of 95.9%, a specificity of 92.3%, a PPV of 93% and an NPV of 95% for the stool antigen test and is in consistency with some newer studies. [27][28][29] So the current study shows that HpSA test can be a reliable tool for diagnosis of H. pylori infection.…”
Section: Dovepressmentioning
confidence: 69%
See 1 more Smart Citation
“…This result is very similar to that of another study performed in Bangladesh, which showed a sensitivity of 95.9%, a specificity of 92.3%, a PPV of 93% and an NPV of 95% for the stool antigen test and is in consistency with some newer studies. [27][28][29] So the current study shows that HpSA test can be a reliable tool for diagnosis of H. pylori infection.…”
Section: Dovepressmentioning
confidence: 69%
“…26 The detection of antigens in the stool by ELISA has shown in various studies to be an effective diagnostic test owing to its high specificity and sensitivity seen in various studies. [27][28][29] In infected individuals, H. pylori sticks to the gastric epithelial wall and is excreted in the feces, thus is a direct test of initial infection and is in superiority of serologic tests. 30 The stool antigen (HpSA) test is simple, rapid, reliable, non-invasive, hazard free and comparatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…The relative risk of gastric cancer in an H. pylori -positive group is 1.7–5.3 times higher than that in an H. pylori -negative group [ 8 ]. However, only 10%–20% of infected patients develop severe diseases during their lifetime [ 9 ]. In the global population, approximately 50% of infected H. pylori varied by prevalence, age, country, ethnic background, and socioeconomic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Among 790 subjects, 768(97.2%) used to take PPI and among them 298(38.8%) was positive for stool antigen (Table I 16 In a hospital-based study stool antigen positivity rate was 51% in 2008-2009 among dyspeptic patients. 23 In our hospital-based study stool antigen positivity for H. pylori is 38.5% among dyspeptic patient. By RUT, H.pylori infection rates in dyspeptic patients were 78% in 2012-2013 and 43.6% in 2015.…”
Section: Resultsmentioning
confidence: 69%